Presence of Plasmodium falciparum strains with artemisinin-resistant K13 mutation C469Y in Busia County, Western Kenya - Makau, M.; Kanoi, B.N.; Mgawe, C.; Maina, M.; Bitshi, M.; Too, E.K.; Naruse, T.K.; Abkallo, Hussein M.; Waweru, H.; Adung'o, F.; Kaneko, O.; Gitaka, J. (Springer, 2024)
Malaria remains a key health and economic problem, particularly in sub-Saharan Africa. The emergence of artemisinin drug resistance (ART-R) parasite strains poses a serious threat to the control and elimination of this scourge. This is because artemisinin-based combination therapies (ACTs) remain the first-line treatment in the majority of malaria-endemic regions in Sub-Saharan Africa. Certain single-nucleotide polymorphisms in the propeller domains of Plasmodium falciparum Kelch 13 protein (K13) have been associated with delayed parasite clearance in vivo and in vitro. These mutations serve as vital molecular markers for tracking the emergence and dispersion of resistance. Recently, there have been increasing reports of the emergence and spread of P. falciparum ART-R parasites in the Eastern Africa region. This necessitates continued surveillance to best inform mitigation efforts. This study investigated the presence of all reported mutations of K13 propeller domains in the parasite population in Busia County, Kenya, a known malaria-endemic region. Two hundred twenty-six participants with microscopically confirmed uncomplicated malaria were recruited for this study. They were treated with artemether–lumefantrine under observation for the first dose, and microscopic examination was repeated 1 day later after ensuring the participants had taken the second and third doses. P. falciparum DNA from all samples underwent targeted amplification of the K13 gene using a semi-nested PCR approach, followed by Sanger sequencing. The recently validated ART-R K13 mutation C469Y was identified in three samples. These three samples were among 63 samples with a low reduction in parasitemia on day 1, suggesting day 1 parasitemia reduction rate is a useful parameter to enrich the ART-R parasites for further analysis. Our findings highlight the need for continuous surveillance of ART-R in western Kenya and the region to determine the spread of ART-R and inform containment.